2020
DOI: 10.1096/fj.202001032r
|View full text |Cite
|
Sign up to set email alerts
|

Laser irradiation decreases sclerostin expression in bone and osteogenic cells

Abstract: Anti‐sclerostin monoclonal antibody romosozumab, a treatment for osteoporosis, reduced vertebral fracture risk and clinical fracture. Laser irradiation triggers various effects, including bio‐stimulation, which can induce beneficial therapeutic effects and biological responses. Originally, we performed in vivo experiments to clarify the mechanism of better bone healing in laser‐ablated bone. Here, we evaluated comprehensive and sequential gene expression in Er:YAG laser‐ablated, bur‐drilled, and nontreated con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Interestingly, in the laser-treated bone tissue, the irradiation increased Dmp1 expression, and suppressed Sost expression, the gene of Sclerostin that inhibits caronical wnt signaling pathway and suppresses new bone formation. They [56] also confirmed using primary rat osteogenic cells (osteocytes-like cells from osteoblast-like cells differentiation) that Er:YAG laser irradiation at 1.5 and 3.1 J/cm 2 decreased Sost expression in the cells and Sclerostin expression in the cultured supernatant, suggesting that Er:YAG laser irradiation may promote bone formation via the suppression of Sost expression.…”
Section: Effects Of Lasersmentioning
confidence: 62%
“…Interestingly, in the laser-treated bone tissue, the irradiation increased Dmp1 expression, and suppressed Sost expression, the gene of Sclerostin that inhibits caronical wnt signaling pathway and suppresses new bone formation. They [56] also confirmed using primary rat osteogenic cells (osteocytes-like cells from osteoblast-like cells differentiation) that Er:YAG laser irradiation at 1.5 and 3.1 J/cm 2 decreased Sost expression in the cells and Sclerostin expression in the cultured supernatant, suggesting that Er:YAG laser irradiation may promote bone formation via the suppression of Sost expression.…”
Section: Effects Of Lasersmentioning
confidence: 62%
“…Bone tissue shows splendid adaptability to mechanical stress, as revealed by Wollf's law (12). Our prior results on the effects of CO 2 laser irradiation on sclerostin expression in osteocytes showed that the effect of CO 2 laser irradiation on bone formation was the same as that of mechanical stress (13). CO 2 laser irradiation has been confirmed to induce bone formation,…”
Section: Discussionmentioning
confidence: 87%